Bioactivity and phenolics profile of aqueous and ethyl acetate extracts of Satureja kitaibelii Wierzb. ex Heuff. obtained by ultrasound-assisted extraction - Kristina Gopčević; Slavica Grujić; Jelena Arsenijević; Ana Džamić; Ivona Veličković; Lidija Izrael-Živković; Ana Medić; Jelena Mudrić; Marina Soković; Ana Đurić (Scientific Reports, 2022)
Abstract The aim of the study was to investigate the biological activity and chemical composition of Satureja kitaibelii Wierzb. ex Heuff. LC–PDA/MS analyses for the aqueous extracts (A1-stem, leaves and flowers, A2-leaves and flowers) and ethyl-acetate extracts (E1-stem, leaves and flowers, E2-leaves and flowers) obtained by ultrasound-assisted extraction enabled the identification of thirty-four compounds. Quantitative analysis revealed that the aqueous extract obtained from leaves and flowers was the richest in total phenolic acids (65.36 mg/g) and flavonoids (21.17 mg/g). The total polyphenol content was the highest in the aqueous extract obtained from leaves and flowers (274 ± 2.4 mg Gallic Acid equivalents/g). The best antioxidant activity was observed for the same extract using the DPPH (SC50 20 ± 10 µg/mL), ABTS (2.834 ± 0.02 mg Ascorbic Acid/g), FRAP (1.922 ± 0.03 mmol Fe2+/mg), and total reducing power tests (16.4 ± 1.0 mg Ascorbic Acid/g). Both ethyl acetate extracts were the most active against strains of Bacillus cereus and Micrococcus flavus (MIC 1.70–1.99 mg/mL and 1.99–3.41 mg/mL, respectively). They were more efficient against Aspergillus ochraceus (MFC 0.86 mg/mL) and towards HeLa cell lines. All the obtained results implied the good potential of the investigated extracts to be used as effective preservatives and functional ingredients in food products and dietary supplements.